Teaching and learning : pedagogy, curriculum and culture - Moore, Alex, 1947- (Routledge, 2012)
"Teaching and Learning: Pedagogy, Curriculum and Culture is designed to share important theory with readers in an accessible but sophisticated way. It offers an overview of the key issues and dominant theories of teaching and learning as they impact upon the practice of education professionals in the classroom. This second edition has been updated to take account of significant changes in the field; young people's use of digital technologies, the increasing involvement of world of business in state education, and ongoing high-profile debates about assessment, to name but a few. It examines the global move from traditional subject-and-knowledge based curricula towards skills and problem-solving and discusses how the emphasis on education for citizenship has forced us to reconsider the social functions of education. Central topics also covered include: - An assessment of the most influential theorists of learning and teaching - The ways in which public educational policy impinges on local practice - The nature and role of language and culture in formal educational settings - An assessment of different models of 'good teaching' - Alternative models of curriculum and pedagogy. With questions, points for consideration and ideas for further reading and research throughout, this book delivers discussion and analysis designed to support understanding of classroom interactions and to contribute to improved practice. It will be essential reading for all student teachers, those engaged in professional development and Education Studies students"--